2013
DOI: 10.1021/ja311923z
|View full text |Cite
|
Sign up to set email alerts
|

Iron(II)-Catalyzed Intramolecular Aminohydroxylation of Olefins with Functionalized Hydroxylamines

Abstract: A diastereoselective aminohydroxylation of olefins with a functionalized hydroxylamine is catalyzed by new iron(II) complexes. This efficient intramolecular process readily affords synthetically useful amino alcohols with excellent selectivity (dr up to > 20:1). Asymmetric catalysis with chiral iron(II) complexes and preliminary mechanistic studies reveal an iron nitrenoid is a possible intermediate that can undergo either aminohydroxylation or aziridination, and the selectivity can be controlled by careful se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(56 citation statements)
references
References 83 publications
(22 reference statements)
2
50
1
Order By: Relevance
“…Han observed trans difunctionalization of cycloalkenes in the studies of oxime and hydrazone radical addition reactions 4c,d. Recently, Xu reported an iron‐catalyzed method and demonstrated trans selectivity with a cyclohexenyl substrate 4e…”
Section: Methodsmentioning
confidence: 99%
“…Han observed trans difunctionalization of cycloalkenes in the studies of oxime and hydrazone radical addition reactions 4c,d. Recently, Xu reported an iron‐catalyzed method and demonstrated trans selectivity with a cyclohexenyl substrate 4e…”
Section: Methodsmentioning
confidence: 99%
“…They are also of great importance as chiral building blocks for chemical synthesis and L - threo -3,4-dihydroxyphenylserine (Droxidopa) is itself a (pro)drug used in the treatment of Parkinson’s disease 5 . Although many different synthetic methods have been reported for their chemical synthesis—including methods based on glycine enolates 6 , glycinamides 7 , glycine Schiff’s base 8 and the aminohydroxylation of olefins 9 —the production of β-hydroxy-α-amino acids by enzymatic means is particularly attractive as these can set two stereocentres in a single reaction that can be performed in a one-pot process with minimal protection of substrates and under mild, aqueous conditions. One such example is found in the threonine aldolases (TAs) although their utility is limited due to low synthetic yields and modest diastereoselectivity (they are highly stereoselective for the α-carbon) 10 11 12 .…”
mentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53] Recently, we discovered dioxazolones can undergo intermolecular N-N coupling with arylamines to make hydrazides under either iridium or iron catalysis. [54][55][56][57][58][59][60][61][62][63][64] Mechanistic studies of the Ir-catalyzed system indicated an outer-sphere nucleophilic attack of the nitrogen group of Ir-nitrenoid intermediate by amine leads to the N-N coupling product.…”
Section: Resultsmentioning
confidence: 99%